Effects of a behavioural approach on lifestyle habits in a healthy Italian population: a before-after interventional study - Guberti, E.; Lorini, C.; Cavallo, G.; Navacchia, P.; Marzocchi, R.; Bonaccorsi, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The study aimed to assess the effectiveness of an educational intervention promoting adherence to healthy diet and physical activity.Study design. Before-after interventional study. Methods. Participants were healthy volunteers, 18-70 y old, from Bologna. They followed a training course consisting of seven meetings and signed a contract to comply with the promoted habits, verified through questionnaires at the engagement phase (T0), three months later (T1) and one year later (T2). Results. One hundred, fifty-three subjects were involved, 75.8% were evaluated at T1 and 41.2% at T2. More than 80% of the subjects involved at T1 achieved an improvement of planned goals. Moreover, 77% of T1 compliants retained healthy eating and physical activity at T2.Conclusions. The proposed pathway of empowerment positively affected nutrition and promotion of physical activity at 3 months after the intervention (T1) and were maintained even after a year. The results appear to be promising for primary prevention across the spectrum of a healthy lifestyle educational approach.